2020
DOI: 10.1007/s42773-020-00049-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochar as adsorbent in purification of clear-cut forest runoff water: adsorption rate and adsorption capacity

Abstract: Forest management practices in boreal peatlands increase nutrient export and suspended solids to watercourses calling for development of new water protection methods. One potential solution could be adsorption-based purification of runoff water using biochar. The aim of this study was to determine the adsorption rate and capacity for Norway spruce and silver birch biochars to design a biochar-filled reactor for a ditch drain. In a 10-day laboratory experiment, biochar was stirred with runoff water from a clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
(51 reference statements)
4
20
0
Order By: Relevance
“…The current study showed that birch and spruce biochar effectively adsorbed TN and NO 3 − -N in forest runoff waters. Our results support previous studies by Saarela et al (2020) andKakaei Lafdani et al (2020).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The current study showed that birch and spruce biochar effectively adsorbed TN and NO 3 − -N in forest runoff waters. Our results support previous studies by Saarela et al (2020) andKakaei Lafdani et al (2020).…”
Section: Discussionsupporting
confidence: 94%
“…2 and 3), which is probably due to the increased N availability in the solution and increased TN concentration gradient along the flow path from the solution to external surfaces and finally to internal surfaces of biochar (Lagritte & Pasquier, 2016;Ahmadvand et al, 2018). The results are consistent with the results obtained by Ahmadvand et al (2018) and Saarela et al (2020), showing that with an increase in the initial N concentration of the solution, the adsorption amount of biochar tends to increase. The low initial concentrations of NH 4 + -N (< 0.02 mg L −1 ) was the reason why we could not determine the adsorption parameters for this compound, but based on the literature, it is known that biochar is an effective adsorbent for NH 4 + -N (Wang et al, 2015;Takaya et al, 2016;Yin et al, 2017).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations